Labor adjustment and productivity in the OECD - Maarten Dossche; Andrea Gazzani; Vivien Lewis (European Central Bank (ECB), 2021)
Labor productivity is more procyclical in OECD countries with lower employment volatility. To capture this new stylized fact, we propose a business cycle model with employment adjustment costs, variable hours and labor effort. We show that, in our model with variable effort, greater labor market frictions are associated with procyclical labor productivity as well as stable employment. In contrast, the constant-effort model fails to replicate the observed cross-country pattern in the data. By implication, labor market deregulation has a greater effect on the cyclicality of labor productivity and on the relative volatility of employment when effort can vary.
Keywords: E30; E50; E60; 330; effort; hours; labor adjustment; labor market deregulation; labor productivity